The 15th Kilbrandon Lecture (University of Strathclyde, 23 November 2017) - Nicola Sturgeon (Scottish Journal of Residential Child Care)
It is a pleasure to be here and an honour to give this lecture. I know that in doing so I’m following in some distinguished footsteps – including Sir Harry Burns, Sir Neil MacCormick and of course Donald Dewar, the first First Minister, when he was Secretary of State for Scotland. It is also a pleasure to pay tribute to Lord Kilbrandon. Lord Kilbrandon of course produced a hugely important and influential report on constitutional change in 1974, which led indirectly to the first devolution referendum in 1979. He was also one of the outstanding Scottish judges of his generation. Even if he had never produced his report on children and young people, therefore, there is no doubt he would be remembered fondly today as someone who had a significant, enduring and beneficial impact on modern Scotland. I am delighted that Heather Shaw, his granddaughter, is in the audience this evening. And of course his finest and most lasting achievement – the one we are marking this evening – is the report of 1964 which led to the establishment of the children’s hearings system in 1971.